Factores Familiares Asociados a la Adherencia al Tratamiento en Usuarios de la Fundación Colectivo Aquí y Ahora - Naval Pereyra, Juan Carlos (Universidad Antonio Nariño, 2024)
This study examines the papers of the factors that have made possible that the families make factors adherent to the process the recovery of their sons and the real importance of the support of social reds, the relationship between parents, mothers, and son’s users of the foundation “colective here and now” of the city Bogotá, Colombia. Five families were examined, and of the three programs and the information gived, suggests that they are families with different structures and strategies that have accomplished the rehabilitation of their relative keeps going with time.